UJI KEEFEKTIFAN BEBERAPA BENTUK PERANGKAP TERHADAP HAMA LALAT BUAH PADA TANAMAN JAMBU BIJI (Psidium guajava L) - Sutikno, Agus; Salbiah, Desita; Ningsi, Sulystia (PEST Tropical Journal, 2013)
Fruit flies are major plant pest in guava. Research aimed at knowing theeffectiveness some trap types forward fruit flies pest at guava plant (Psidiumguajava L). Research is implemented by using a randomized block design (RBD)with 4 treatments and 16 groups, in order to obtain 64 units of the experiment. Thetreatment is on trial is this: a ball, a cube, a card, a cylinderl. The data analysisstatistically to a diverse and tested the real difference to the smallest (bnt).Parameter observed is, identification of the fruit flies trapped, the fruit fliestrapped, sum of fruit flies male, sum of fruit flies female and sex ratio fruit flies.The results show the fruit flies trapped in a furious ball 79,25 flies, which isobtained fruit flies trapped by using a cylinder that 78,25 flies.Keywords: Fruit flies, trap types, ball, cube, cards, a cylinder, Psidiumguajava L.